A curing system of benzoxazine with amine: reactivity, reaction mechanism and material properties1. Issue 25 (21st March 2015) - Sun, JiaQin; Wei, Wei; Xu, YaZhen; Qu, JieHao; Liu, XiangDong; Endo, Takeshi
<x xml:space="preserve">Abstract</x> In addition to providing an acceleration effect on curing, suitable amines react with benzoxazine to form desired structures and improve the materials properties of the cured resins.